Furvina inhibits the 3-oxo-C12-HSL-based quorum sensing system of Pseudomonas aeruginosa and QS-dependent phenotypes - Anabela Borges (2017)
Disruption of cell-cell communication or quorum sensing (QS) is considered a stimulating approach for reducing bacterial pathogenicity and resistance. Although several QS inhibitors (QSIs) have been discovered so far their clinical use remains distant. This problem can be circumvented by searching for QSI among drugs already approved for the treatment of different diseases. In this context, antibiotics have earned special attention. Whereas at high concentrations antibiotics exert a killing effect, at lower concentrations they may act as signaling molecules and as such can modulate gene expression. In this study, the antibiotic furvina was shown to be able to cause inhibition of the 3-oxo-C12-HSL-dependent QS system of Pseudomonas aeruginosa. Furvina interacts with the LasI/LasR system. The data were validated by modeling studies. Furvina can also reduce biofilm formation and decrease the production of QS-controlled virulence factors.